Infecção de ovelhas prenhes com o vírus da diarréia viral bovina tipo 2 (BVDV-2): patogenia e avaliação de proteção vacinal - Scherer, Charles Fernando Capinos (2000)
The pathogenesis of bovine viral diarrhea virus type 2 (BVDV-2) infection and the serological response and fetal protection induced by vaccination were studied in pregnant ewes. In the first experiment, the reproductive effects of BVDV-2 infection were investigated in pregnant ewes inoculated with a Brazilian non-cytopathic BVDV-2 isolate (SV-260) at three stages of gestation. A few ewes presented a transient viremia, accompanied by a transient and mild hyperthermia and nasal discharge. Some ewes were sacrificed at different time-points after virus inoculation to study the kinetics of fetal infection. Infectivity and viral antigens were detected in placentomes from day 7 to 36 post-inoculation (pi) and in fetal fluids and tissues between days 10 and 28 pi. Cardiac petechial hemorrhages and hemoperitonium accompanied by a severe fibrinous ulcerative placentitis were observed in fetuses examined at days 21, 28 and 36 pi. Virus inoculation at days 55-60 of gestation resulted in a prolonged virus replication in placentomes and fetal tissues; ewes that were allowed to proceed with pregnancy had 77% of abortions or fetal and perinatal deaths. Seven lambs (stillbirths, unviable and viable) born to these ewes were virus positive at birth; virus was recovered repeatedly from leukocytes from two lambs up 2 and 6 months of age, respectively, indicating they were persistently infected. Ewes inoculated at days 65-70 of gestation had 66.6% of fetal and perinatal losses. Three viable lambs born to these ewes were healthy, BVDV antibody-positive and virus-negative. Virus inoculation at days 120-125 of gestation induced a transient viral replication in placentomes and in a few fetal tissues, followed by the rise of fetal neutralizing antibodies and virus clearance. Lambs born to these ewes were healthy, antibody-positive and virus-negative. These results demonstrate that the biology of BVDV-2 infection in pregnant sheep is essentially similar to that of BVDV-1 in pregnant cattle and sheep. In a second experiment, the serologic response and fetal protection conferred by three BVDV inactivated vaccines (vaccines A, B and C) were evaluated through immunization followed by challenge of pregnant ewes with Brazilian BVDV-1 and BVDV-2 field isolates. Moderate to low levels of anti-BVDV-1 neutralizing antibodies were detected in most animals (45/47) 30 days after the second vaccine administration. In contrast, neutralizing activity to BVDV-2 was not detected in several vaccinated animals (12/47) and was significantly lower than to BVDV-1 in all three vaccine groups. The mean antibody titers against the challenge viruses declined significantly by day 180, such that several animals had no detectable antibody against BVDV-1 (group B-1/19;C-8/14) and mainly against BVDV-2 (A=7/14; B= 13/19; C= 13/14). The antibodies produced by vaccination were not sufficient to prevent replication, viremia and transplacentary transmission of the virus to the fetuses in all ewes from the different vaccine groups upon challenge. These results demonstrate that the vaccines induced low to moderate titers of antibody against BVDV-1 and even lower titers against BVDV-2 in most animals. The antibody levels declined progressively and were not sufficient to prevent fetal infection upon challenge with BVDV-1 and BVDV-2 at day 180. In addition, these findings demonstrate that pregnant sheep represent an adequate model to study fetal protection by BVDV vaccines.